Back to the future? Macroprudential policy and the rebirth of local authority mortgages in Ireland - Conor O'Toole; Rachel Slaymaker (The Economic and Social Research Institute (ESRI), 2020)
The global financial crisis heralded a new era of macroprudential mortgage regulations such as loan-to-value and loan-to-income restrictions. Such measures safeguard the financial system but can lead to credit access difficulties, in particular for first-time buyers. In this paper, we examine the introduction of a direct public mortgage, the Rebuilding Ireland Home Loan, which aims to address these dfficulties in Ireland. We use new unique granular microdata for applications to the scheme to explore the relationship between households applying to the scheme and the broader commercial market. We show that RIHL applicants, particularly those in urban areas, are under-served by the commercial market as they cannot borrow sufficient amounts due to the regulatory framework. The scheme enables these lower to middle-income borrowers to access mortgage credit and thus directly targets the externality from the regulatory regime. We argue that these public, local authority loans, once accompanied by suffcient safeguards, can be an essential tool to bridge credit gaps while ensuring the commercial banks are subject to strong macroprudential rules.
Keywords: R21; G21; R31; R38; 330; Access to credit; macroprudential policy; mortgages